A study of the Resilience Analysis Grid method and its applicability to the water sector in England and Wales. (20th November 2019) - Rodríguez, Mayra; Lawson, Elizabeth; Butler, David
Abstract: This paper presents an adaptation of the Resilience Analysis Grid (RAG) method framed on the Resilience Engineering theory as a proposal for tackling the lack of organisational resilience metrics in the water sector of England and Wales. The method was adapted to the sector by selecting 16 indicators and the addition of a 'Resilience Ethos' section to the grid. Its applicability was tested by analysing the evolution of resilience in Ofwat's Price Reviews 2009 (PR09), 2014 (PR14) and 2019 (PR19). Key conclusions obtained were that: (I) PR14 acts as a pivot between PR09 and PR19, as it installs a new regulatory approach; (II) the sector has advanced significantly towards greater consideration of resilience and its management in PR19; and (III) the PRs lack instruments for in‐period performance assessment. The RAG method proved to be simple and flexible to use, delivering clear and straightforward graphical results.